First results from AAVS 0.5: A prototype array for next-generation radio astronomy - Hall, Peter; Sutinjo, Adrian; de Lera Acedo, E.; Wayth, Randall; Razavi-Ghods, N.; Colegate, Timothy; Faulkner, A.; Juswardy, Budi; Fiorelli, B; Booler, Tom; Bij de Vaate, J.; Waterson, Mark; et al. (IEEE Xplore, 2013)
This paper provides an overview of the Aperture Array Verification System 0.5 (AAVS 0.5), co-located and operated in conjunction with the Murchison Widefield Array (MWA) near the Australian SKA core site. AAVS 0.5 is based on log-periodic antennas of a type potentially useful in next-generation low-frequency arrays such as SKA-low. We report on our progress by discussing results obtained thus far as well as test plans for the near future. A number of lessons learned will be presented, demonstrating that hands-on experience constitutes an essential knowledge-base in the pre-construction phase of a radio-telescope such as the SKA.